Demand and Status of a Scientific Degree in the Non-Academic Labour Market: Regional Case - O. S. Ivanchenko; V. V. Sych (Высшее образование в России)
Technological leadership and innovation-driven growth have actualized the request for highly qualified personnel, which have recently been associated with holders of a scientific degree. In the academic field, a scientific degree is a testimony to the occupational status and an integral feature of professional growth and advancement. The reasonableness and significance of a scientific degree in the non-academic market are ambiguous. The purpose of this article is to investigate the opinion and assessments of the non-academic sphere representatives about the demand for the employees with a scientific degree and the status of a scientific degree outside the academic labour market. The research was conducted using the method of semi-structured interview with employers and representatives of seven enterprises in the south of Russia in the machine engineering, metalworking, ferrous metallurgy and IT sectors (n = 13). As a result of the study it was established that: in employment a scientific degree does not give competitive advantages to the applicant; a scientific degree has no value in the non-academic labour market, does not contribute to the advancement and occupation of a higher position in the enterprise; a scientific degree and the presence of employees with a scientific degree in the staff are considered as image-building, status marker and reputation capital of the enterprise; employers have stereotypes regarding scientific employees, which are associated both with the individual organization of labour processes and the compatibility of the scientific, creative and production process; the non-academic sector lacks a human resources strategy for dealing with such employees and a system of their incentives. The authors conclude that the demand for a scientific degree in the non-academic labour market is caused largely by a political request related with the belief that technological and innovative breakthroughs can provide highly qualified personnel with a scientific degree. The authors focus on the probable risks associated with the massification of degree holders, that can lead to a blurring of academic culture and loss of identity of the scientific community.